Pengaruh Temperatur Padapenyambungan Material Polyethylene (PE) Menggunakan Metode Friction Stir Welding - Anjananda Vitodi; Dodi Sofyan Arief; M. Dalil (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Friction Stir Welding (FSW) is a welding process that is promoted with little cost and good connection quality. That is because it does not need filler metal and can eliminate or minimize the number of cracks and porosity defects. The FSW principle uses tools that rotate and move across so that the material occurs forging at the center of the weld and finally melts. The FSW welding process variables are tool parameters and welding parameters. Welding parameters include rotational speed, tool slope, travel speed, shoulder penetration, probe penetration, probe shape and dimensions, shoulder shape and dimensions, material tools, and others. In this study, the effect of temperature variation of heating elements used in welding polyethylene (PE) material on tensile strength by tensile test is examined. From the tensile test data, it is found that the higher the temperature of the heating element during the FSW process, the feeding translation tool will increase and the tensile strength of the FSW joint results will also increase and vice versa. The lowest tensile strength occurs at temperatures of 0 ° C (without preheating) and 100 ° C (using preheating), namely 4.465 MPa and 14.25 MPa. The highest tensile strength occurs at heating element temperature of 140 ° C which is 24.71 MPa while the tensile strength of polyethlyene material without FSW connection is 29 MPa.Keyword : friction stir welding, feed rate, polyethylene, the tensile strength of welded joints.